EFFECTIVENESS OF THE PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION METHOD APPLICATION ON UPPER LIMB FUNCTIONS IN PATIENTS AFTER STROKE: A SYSTEMATIC REVIEW OF LITERATURE - Kaminska, Anastasija; Sargsjane, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The brain damage caused by a stroke can lead to severe and long-lasting physical and mental health problems, which can have a significant impact on human quality of life. Although restoring gait parameters in stroke patients is one of the most important rehabilitation goals, currently around 80% of stroke survivors have some degree of upper limb motor impairment. Several authors have shown that restoration of upper limb function is often more difficult to achieve and requires a longer rehabilitation period. Proprioceptive neuromuscular facilitation (PNF) is thought to be one of the most common neurophysiological techniques used by physiotherapists in post-stroke rehabilitation. The aim is to evaluate the effectiveness of proprioceptive neuromuscular facilitation (PNF) in improving upper limb function in patients after stroke through a systematic literature review. The research inquiry was performed by searching through various online databases until February 2023. Following the PRISMA 2020 guidelines, studies were selected using the PICO model and its elements, and based on the inclusion and exclusion criteria. The quality of the selected studies was assessed using the PEDro scale. The review examined five studies on PNF effects in 210 stroke patients, all scoring six or more on the high-quality PEDro scale. Patients were, on average, 52 to 63 years old. Four of the five studies, using the Arm Motor Ability Test and Fugl-Meyer assessment, showed statistically significant improvements in upper limb motor ability and function post-PNF intervention. One study assessing self-care functional ability revealed significant improvements in the Barthel index for both experimental and control groups. Spasticity assessment with the Ashford scale in one study indicated a statistically significant reduction in upper limb spasticity in both groups. Yeole et al. found significant improvements in active range of motion using a manual goniometer in shoulder and elbow joints and wrist joint flexion, extension, and radial deviation for PNF-applied participants.